KEBERMAKNAAN LEKSEM BERMAKNA ROBEK DALAM BAHASA INDONESIA - Hari Sulastri (Universitas Nasional, 2016)
ABSTRACTThis paper discusses the significance of leksem torn in Indonesian. The purpose of this paper is to see how close themeaningfulness contained in a meaningful leksem torn in Indonesian. Methods and techniques in this paper usesdescriptive method with qualitative done in several stages, namely data collection, data analysis, and presentationof the results of the analysis. In addition, the paint of techniques and pengartuan from various sources Keywords: meaninfulness, leksem, and torn